Microcapsules and Transdermal Patch: A Parallel Access for Improved Delivery of Antidiabetic Drug - Saxena, Preeti (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Microcapsules and transdermal patch: A parallel access for improved delivery of antidiabetic drug. Materials and Methods: Different formulations were formulated employing sodium alginate (SA) alone or in combination with various coating polymers. Alginate coated microcapsules of gliclazide were prepared by dispersing the drug (15 mg) into aqueous solutions of SA under constant stirring. Preparation of transdermal patches (TDP): Glibenclamide (GL)-loaded TDP formulations were prepared by solvent casting method with slight modification. Hydroxypropyl methylcellulose was dissolved in a mixture of acetone/isopropyl alcohol/ethanol (50:30:20) with continuous stirring in a closed system at 25Â°C. Evaluation of the prepared microcapsules: Microscopical examination and particle size measurement of gliclazide microcapsules were done using an optical microscope. The prepared microcapsules were mounted in few drops of distilled water and examined under an optical microscope. Evaluation of TDP: Several steps such as moisture intake, moisture uptake, and weight variation are used for evaluation method. Conclusion: From the comparative study, it was concluded that the transdermal system of GL produced better improvement compared to oral microcapsule administration.